Rapid detection of porcine dna by real-time polymerase chain reaction (qpcr) on imported processed foods - Wardani, Agustin Krisna; ., Reza; Rifani, Aisyi Sakina; Sutrisno, Aji; Brahmanti, Ajeng Astrini (Penerbit UiTM, 2022)
A pair of porcine-specific primers defining a 145 bp region of the mitochondrial D-loop 443 were used to identify the presence of porcine DNA in ten samples of imported instant noodles and soft candies by Real- Time Quantitative Polymerase Chain Reaction (qPCR). This study was performed in three steps: sample preparation, DNA extraction, and DNA amplification using Real-Time PCR. The porcine DNA was amplified at an annealing temperature of 53oC for 39 cycles. The result confirmed that three samples of instant noodles and three soft candies were found to contain porcine D.N.A. This method could effectively authenticate Halal products in processed foods, verify food labelling, and provide consumer protection.